INTRINSIC ELEMENTS ANALYSIS OF THE MOVIESCOTT PILGRIM VS. THE WORLD - Umboro, Priyo Danu (Jurnal Ilmiah Spectral, 2021)
This study aims to find out the intrinsic elements used in the movie Scott Pilgrim vs. The World and to determine how intrinsic elements relate to each other in the movie. This study used a qualitative method in researching which data are taken from utterances, dialogues, and narrations in the form of screenshots of the movie. This study found the movie Scoilgrim vs. The World used the plot, settings, characters and theme as intrinsic elements. This study also found the intrinsic elements related to each other by the plot changes when a character was introduced. A new character when the setting of the place changed and the plot determined the theme of the movie.